Bottomonium at Non-zero Temperature from Lattice Non-relativistic QCD - RYAN, SINEAD (My University, 2012)
The temperature dependence of bottomonium states at temperatures above and below $T_c$ is presented, using non-relativistic dynamics for the bottom quark and full relativistic lattice QCD simulations for two light flavors on a highly anisotropic lattice. We find that the S-waves ($\Upsilon$ and $\eta_b$) show little temperature dependence in this range while the P wave propagators show a crossover from the exponential decay characterizing the hadronic phase to a power-law behavior consistent with nearly-free dynamics at approximately twice the critical temperature.
AIP Conference Proceedings
Particles & Nuclei International Conference (PANIC 2011)
PUBLISHED
Massachusetts Institute of Technology
Keywords: Particles and fields physics; Bottomonium